ADMINISTRATIVE JUSTICE IN POLAND - J. Turłukowski (BRICS Law Journal, 2016)
This article begins with an analysis of the development of administrative justice in Poland over the last centuries. In particular, the author examines administrative jurisdiction before 1918, when Poland regained its independence, the period of the Duchy of Warsaw, the Kingdom of Poland, and the practice on Polish territory under Austrian and Prussian control. The author then moves to modern law by presenting the judicial system in Poland in general, especially the differences between the separate systems of general courts and administrative courts, and analyses the jurisdiction of voivodship (regional) administrative courts, and the basic principles of judicial and administrative proceedings. The focus of study is mainly devoted to judicial and administrative procedure, rather than an administrative process of citizens before administrative authorities regulated in a separate Code of Administrative Procedure. The article describes the role of the judge (pointing out the differences between the active role of first instance judges and the limited capabilities of the judges of the appeal) and the powers of the Supreme Court, in particular its power to adopt resolutions, which has agreat importance for the unification of the jurisprudence. A brief analysis is given to class actions, which in the Polish legal system are inadmissible in court and administrative proceedings. The articles provides a statistical cross-section illustrating the role of administrative jurisdiction. The author concludes with observations pointing up the progress of administrative jurisdiction in Poland, not only in the legal sense, but also in the cultural sense.